Collective identity, solidarity and trust as constructs of mass mobilization in the Eastern European borderzone - Khyzhniak, Oleksandr (Ukrainian Sociological Journal, 2017)
This article is devoted to identifying the role of collective identity, collective solidarity and trust in the dynamics of contemporary Eastern European borderzone. Characteristics and perspectives of mass mobilization in the Eastern European borderzone are determined by the peculiarities of the Borderzone: by social composition of its people, their mental traits, institutional and socio-cultural factors. Development of the Eastern European borderzone depends on how collective identity, collective solidarity and trust will be implemented in the process of mass mobilization during social intercultural interactions. The thesis that mass mobilization gives dynamism to the processes of registration of Eastern European Borderzone appearance is proved. The mass mobilization is based not only on socio-economic factors, but also has socio-cultural component. The role of identity, solidarity and trust in the collective social action aimed at mass social mobilization is determined. The author’s concept is that the constructs of mass mobilization in the Eastern European borderzone become, firstly, the collective identity that sets the limits of collective action, distinguishes its participants and non-participants; secondly, the collective solidarity, which provides steady motivation for collective action; thirdly, the trust that serves to integrate its members in the collective social action.